The accused [videorecording (DVD)] - Kaplan, Jonathan, 1947-; Foster, Jodie; McGillis, Kelly, 1957- (Paramount Home Entertainment, 2006)
Sarah Tobias is gang raped in a neighborhood bar. She finds herself battling the legal system twice as she and her attorney (McGillis) go after both her attackers and the onlookers whose cheering fueled and encouraged the assault. This film is based on a true story.